"Guest in the house" - Brahm, John, 1893-1982; Baxter, Anne; Wilde, Hagar; Hunt Stromberg Productions; Cinetel Films ([Los Angeles, CA] : Hunt Stromberg Productions, 1944)
Evelyn, an emotionally vulnerable and unstable woman, stays at the home of her doctor Dan Proctor. There she meets and falls in love with his brother, Douglas, who is happily married to Ann. Evelyn then sets forth to break up the happy marriage and win the love of Douglas, with tragic results. --
Originally released by United Artists.
Based on the play: Guest in the house / by Hagar Wilde & Dale Eunson.
Anne Baxter, Ralph Bellamy, Aline MacMahon, Ruth Warrick, Scott McKay, Marie McDonald.
Cinematographer, Lee Garmes; editor, Walter Hannemann; music, Werner Janssen.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015)
Keywords: Mentally ill women -- Drama; Thrillers (Motion pictures); Film noir; Feature films; Internet videos; Streaming video